2014
DOI: 10.1016/j.jpainsymman.2013.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Assessment of the MSAS-SF and the FACIT-Fatigue Scale in Spanish-Speaking Patients With Cancer in Uruguay

Abstract: The study showed that both the MSAS-SF and the FACIT-Fatigue have good reliability and validity for use with patients with cancer in Uruguay. When used simultaneously, these instruments may provide a complete picture of the impact of cancer and its treatment on the patient's quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…The internal consistency reliability of the Arabic version of the FACIT-Fatigue was a ¼ 0.94, which was higher than the original study of Yellen et al 6 (a ¼ 0.93). The internal consistency of the FACIT-Fatigue in Spanish was 0.88, 8 in Brazilian it was 0.79, 13 among patients diagnosed with almost similar cancers. The FACT-G subscales, PWB, SWB-6, EWB-5, and FWB, also had good reliability estimates (0.73 to 0.92) with total internal consistency of a ¼ 0.92; this is in comparison with the result of the original version, which was a ¼ 0.89.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The internal consistency reliability of the Arabic version of the FACIT-Fatigue was a ¼ 0.94, which was higher than the original study of Yellen et al 6 (a ¼ 0.93). The internal consistency of the FACIT-Fatigue in Spanish was 0.88, 8 in Brazilian it was 0.79, 13 among patients diagnosed with almost similar cancers. The FACT-G subscales, PWB, SWB-6, EWB-5, and FWB, also had good reliability estimates (0.73 to 0.92) with total internal consistency of a ¼ 0.92; this is in comparison with the result of the original version, which was a ¼ 0.89.…”
Section: Discussionmentioning
confidence: 92%
“…FACIT-F 40-items has been validated for use with a variety of cancer diagnoses and treatments; the original scale showed strong internal consistency (coefficient alpha 0.93e0.95) and good stability (test-retest, r ¼ 0.87). 6 Other studies using the instrument have translated it into Spanish, 8 French and Dutch, 9 Japanese, 10 Persian, 11 and Portuguese. 12,13 The internal consistency in the translated versions ranged from 0.79 to 0.94.…”
Section: Introductionmentioning
confidence: 99%
“…The scoring procedure follows the instructions of Portenoy et al for the short form [25]. The MSAS-SF has been cross-culturally adapted to Spanish speakers and has shown adequate psychometric properties [26]. It has been widely used in patients with ACKD [1820].…”
Section: Methodsmentioning
confidence: 99%
“…GI symptom reports in the solid tumor population are mixed, with 5 of 10 MSAS GI symptoms rated 2 or greater in severity and none of the GI symptoms rated 2 or greater in distress among women with breast cancer (Hofsø, Miaskowski, Bjordal, Cooper, & Rustøen, 2012). Dapueto, Abreu, Francolino, and Levin (2014) reported that all 10 GI symptoms had a mean distress rating of 2 or greater in patients with various solid tumor diagnoses.…”
Section: Gi-gastrointestinalmentioning
confidence: 99%
“…One possible explanation for the low symptom severity and distress reports in the sample could be related to proactive symptom prevention efforts. The research done by Hofsø et al (2012), Dapueto et al (2014), and Bolukbas and Kutluturkan (2014) all took place outside of the United States, where supportive medication regimens may be different than those offered in U.S. hospitals and clinics. None of these studies reported the symptom management medications their participants may have received.…”
Section: Gi-gastrointestinalmentioning
confidence: 99%